Inflation, price stability, and monetary policy: On the legality of inflation targeting by the Eurosystem - Helmut Siekmann (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2022)
In the communication of the European Central Bank (ECB), the statement that "we act within our mandate" is often referred to. Also among practitioners of the Eurosystem the term "mandate" has become popular. In his Working Paper, Helmut Siekmann analyzes the legal foundation of the tasks and objectives of the Eurosysstem and price stability as a legal term. He finds that the primary law of the EU only very sparsely employs the term "mandate". It is never used in the context of monetary policy and its institutions. Moreover, he comes to the conclusion that inflation targeting as a task, competence, or objective of the Eurosystem is legally highly questionable according to the common standards of interpretation.
Keywords: 330